2021
DOI: 10.1007/s00431-021-04002-5
|View full text |Cite
|
Sign up to set email alerts
|

Are psychological symptoms a risk factor for musculoskeletal pain in adolescents?

Abstract: Adolescent musculoskeletal pain is common and is associated with musculoskeletal pain in adulthood. Psychological symptoms, also common in adolescence, have been shown to be associated with musculoskeletal pain, but the current evidence is mixed and may be dependent on effect modifiers. This study investigated whether adolescents with psychological symptoms (internalizing and externalizing constructs) at age 13 years were at higher odds for musculoskeletal pain at age 17 years and whether the associations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 80 publications
(144 reference statements)
1
1
0
Order By: Relevance
“…Our findings are consistent with the body of evidence indicating that cognitive and emotional psychological factors increase the risk of the development of pain (Huguet et al, 2016;O'Sullivan et al, 2019;Smith et al, 2017). Andreucci et al (2021) reported similar findings suggesting that externalizing symptoms in early adolescence (age of 13), and to some extent internalizing symptoms, increases the odds of having musculoskeletal pain at the age of 17. Psychological distress has been associated with the transition from acute to chronic pain and the development of disabling pain conditions in children and adults (Hasenbring et al, 2001;Huguet et al, 2016;Meints & Edwards, 2018;Smith et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with the body of evidence indicating that cognitive and emotional psychological factors increase the risk of the development of pain (Huguet et al, 2016;O'Sullivan et al, 2019;Smith et al, 2017). Andreucci et al (2021) reported similar findings suggesting that externalizing symptoms in early adolescence (age of 13), and to some extent internalizing symptoms, increases the odds of having musculoskeletal pain at the age of 17. Psychological distress has been associated with the transition from acute to chronic pain and the development of disabling pain conditions in children and adults (Hasenbring et al, 2001;Huguet et al, 2016;Meints & Edwards, 2018;Smith et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Musculoskeletal pain is experienced by up to 40% of adolescents [1][2][3] and is a common reason for consulting a general practitioner (GP), who is often the first healthcare professional involved in the management and treatment of pain. [4][5][6] The knee is one of the most prevalent regions of reported pain.…”
Section: Introductionmentioning
confidence: 99%